Correction: Central venous pressure and dynamic indices to assess fluid appropriateness in critically ill patients: A pilot study. - Chiara Prezioso; Roberta Trotta; Erika Cavallo; Federica Fusina; Elena Malpetti; Filippo Albani; Rosalba Caserta; Antonio Rosano; Giuseppe Natalini (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0285935.].